THE INFLUENCE OF WORKLOAD AND WORKING ENVIRONMENT ON JOB STRESS IN MSME EMPLOYEES IN PALEMBANG - kwanto, ivan; alexander, devin; darmawan, dicky (Universitas Muhammadiyah Tangerang, 2024)
The aim of the writing that I will write is to see wheter there is a relationship between workload variables and the work environment on employee work stress for MSME employees in the Palembang area. In this writing technique, purpusov sampling technique was used which used 89 respondents as sample samples and this data analysis technique used a simple linear regression analysis technique. This technique aims to gain an understanding that is used to see wheter there is a relationship between workload and work environment variables on work stress among MSME employees in Palembang. In this writing we will use hyphothesis testing, namely the T test and the results obtained from this writing are that workload has a significant influence on the work stress of MSME employees in Palembang but the work environment does not have a positive influence on the work stress of MSME employees in Palembang